Optical microfiber sensor for heavy metal ion detection - Yap, Stephanie Hui Kit (2016)
Heavy metal pollution in water environment poses a serious threat and of great environmental concern because they cannot be degraded or destroyed completely. In fact, heavy metal tends to accumulate over time within the living organism and the rate of accumulation can be faster than they are excreted. Therefore, continuous monitoring of the level of heavy metal contaminants in water resources is crucial to keep them below the standard maximum permissible limit of the particular geographical area. Addressing this matter, an optical tapered fiber that is well known for excellent sensing capabilities due to the strong evanescent field in the tapered region was adapted in this study to measure different concentrations of the metal ion in an aqueous environment. Tapered fiber with a waist diameter of 7.1 micrometer was used and the surface of the tapered region was functionalized with the amine group in order to form a strong covalent bond between the amine and the carboxylic group of a compound known as chelating agents. The chelating agent is capable of binding metal ions to form stable metal chelates, thus, when metal ions are bound to the surface of the tapered region, there will be some changes in refractive index around the tapered region. These changes can result in the alteration of the characteristic of light passing through the tapered region.